(untitled) (Fiep Bulletin - online, 2012)
Among the endemic-epidemic diseases, which are major public health problems in Brazil set to hepatitis C. The objective is to assess the epidemiological situation of hepatitis C in Brazil, based on data from the National Disease Information and Notification (SINAN). This is a descriptive study, using data from epidemiological and morbidity in the SINAN period from 2007 to 2010. Based on the results, we observed an increase in the number of diagnosed cases of hepatitis C in 2008 and 2009, followed by a slight decline in 2010. The main source / mechanism of virus infection occurred through intravenous drug use, and the male responsible for the greatest number of cases in all forms of transmission. Regarding age, the age group most affected was 40 to 59 years and the Southeast region with the highest number of reported cases. Yet inconsistencies in the data were observed with respect to age in children under one year and the source / mechanism of infection due to occupational accidents and injecting drug use, and inconsistent data regarding the source / mechanism of infection reported by region of the country. It is concluded that the practice of notification of diseases is a fundamental attitude for improving the delivery of health care, highlighting the need to develop actions in pursuit of continuing education to empower professionals to fill full and correct statement of the mandatory notification as well as information system, enabling better planning of health actions in Brazil.